2012
DOI: 10.1016/j.ijrobp.2012.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High-grade Esophagitis After Definitive Three-dimensional Conformal Therapy, Intensity-modulated Radiation Therapy, or Proton Beam Therapy for Non-small cell Lung Cancer

Abstract: Introduction We analyzed the ability of various patient- and treatment-related factors to predict radiation-induced esophagitis (RE) in patients with non-small cell lung cancer (NSCLC) treated with three-dimensional (3D) conformal radiation therapy (3D-CRT), intensity-modulated radiation therapy (IMRT), or proton beam therapy (PBT). Methods and Materials Patients were treated for NSCLC with 3D-CRT, IMRT, or PBT at MD Anderson from 2000 to 2008 and had full dose-volume histogram (DVH) data available. The endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…This issue has been addressed in a study reported by Gomez et al [29], showing Grade P3 AET in 28% of patients treated with IMRT (N = 139) vs 8% (p < 0.05) of patients treated with 3D-CRT (N = 405). However, another study reported the contrary with equal risks of AET after IMRT or 3D-CRT [30].…”
Section: Discussionmentioning
confidence: 97%
“…This issue has been addressed in a study reported by Gomez et al [29], showing Grade P3 AET in 28% of patients treated with IMRT (N = 139) vs 8% (p < 0.05) of patients treated with 3D-CRT (N = 405). However, another study reported the contrary with equal risks of AET after IMRT or 3D-CRT [30].…”
Section: Discussionmentioning
confidence: 97%
“…In NSCLC during radical chemo-RT, however, oesophagitis and pneumonitis are usually the most significant acute side effects after completion of therapy (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…On long-term follow-up, the development of AE was associated with late esophageal stricture in 15 patients (9%). In another report, IMRT was associated with 28% grade 3 AE (11). Similarly, Kwint et al (12) assessed the AE outcomes in 139 patients with inoperable NSCLC treated with IMRT and concomitant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%